Consumer eWOM communication: The missing link between relational capital and sustainable bioeconomy in health care services - Iuliana Raluca Gheorghe; Victor Lorin Purcărea; Consuela Mădălina Gheorghe (Amfiteatru Economic Journal, 2018)
Today's world faces many challenges that may be solved by using the principles of bioeconomy. Bioeconomy has had a multi-disciplinary approach with the objective of an integrated scope, namely, to achieve sustainable development. In a knowledge-based economy, the link between sustainable bioeconomy and organizations is achieved by Intellectual Capital. The intangible assets of Intellectual Capital coming from the external environment of an organization in the shape of Relational Capital have great value, as they can offer competitive advantages. Consequently, along with the progress of technology and especially the online opinion platforms and Social Media, consumers have begun to share their experiences with other consumers in a new form of communication called electronic word-of-mouth (eWOM). In the health care field, this type of communication triggered a shift in the consumer behavior, leading to their knowledge empowerment about physicians, symptoms and even health care organizations. This study extends the existing literature on health care and Relational Capital by examining the consumers' motives to post eWOM messages in a Romanian Social Media support group, which concentrates on In Vitro Fertilization (IVF) procedures. We identified a number of key motives (reputation, reciprocity, sense of belonging to a community, enjoyment of helping other individuals, moral obligation of helping other individuals with knowledge contribution and knowledge self-efficacy), which may explain the consumers' intentions to post eWOM messages, as integrated in an empirical model. Using the PLS technique, we tested the model on a sample of 121 women, members of the Social Media support group. The findings revealed that 39% of the variance of the intention to post eWOM messages, was explained by reciprocity. The outcomes of this study provide important implications for both research and practice.
Keywords: I12; M39; D64; D71; D81; D83; D91; O34; Q01; 330; bioeconomy; sustainability; health care services; relational capital; eWOM